An approach to geographic information system (GIS) modeling and determination of the quickest route for vegetable delivery / Mohammad Abousaeidi - Mohammad , Abousaeidi (2016)
This study involves the adoption of the Geographic Information System (GIS) modelling approach to determine the quickest routes for delivery of fresh vegetable. The distribution and delivery services of fresh vegetables are a major concern for producers of fresh produce especially concerning transportation. This research focuses on the Sime Darby Company in Malaysia which is producing fresh vegetables. The company is spending a significant part of its budget for a high standard of transportation and delivery services from the depot to hypermarkets. This research develops a spatial database management system based on significant parameters to solve the distribution problem. The optimisation of the model is based on several significant parameters that show the fastest routes for delivery. The main contribution of the developed model is its ability to capture data from different fields to solve distribution problem. This research integrates social data such as population and spatial data such as land use in developing the spatial database management system. Another contribution is to connect this information with digital road networks to select the fastest delivery route. The first objective of this thesis is about to identify the key factors that influence on the selection of the best routes for the distribution purpose. The second one is to develop the Spatial Database Management System and the third one is to develop and propose a GIS model for distribution problem. This PhD thesis presented the implementation of statistical analysis using a linear regression model to identify the key factors affecting driving time. It has been developed several scenarios in order to give the set of alternative fast route in order to distribute fresh vegetables. Among all of the factors in transportation and delivery of fresh product, the focus of this study is on examining the characteristic of transportation such as traffic density, drive time, population, land use and the location of hypermarkets in street network within the study area. The selected routes are chosen in several phases, based on the distance, driving time, average speed, population density, land use, car volume and time-frames as impedances. The final output of this thesis is producing different maps integrated with road networks for decision makers to deliver their fresh vegetables by using the most efficient and fastest routes to reach their intended destinations.